Pengaruh Financial Literacy, Illusion of Control, Overconfidence, Risk Tolerance, dan Risk Perception Terhadap Keputusan Investasi Pada Mahasiswa di Kota Surabaya - PRADIKASARI, ELLEN; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2018)
The development of the capital market along with the increase in Single Investor Identification (SID) makes investment an attractive destination for investors. In investing, investors act rationally or irrational in making investment decisions. So this research aimed to analyze the financial literacy, illusion of control, overconfidence, risk tolerance, and risk perception of investment decisions in students in the city of Surabaya. This research use multiple linier regression analysis technique with 220 respondent sample of university student investor who has Investment Gallery in Surabaya city. The results of this study indicate that the variables overconfidence and risk tolerance effect on investment decisions. Respondents belong to a group of investors who feel confident and like high risks with high returns as well. While the variables of financial literacy, illusion of control and risk perception have no effect on investment decision. Respondents belong to investor groups categorized as higher financial literacy, but respondents feel no need to use knowledge in decision making invetasi. In addition, in this study the average respondent sees historical information, but the information can not predict future changes, so respondents do not have an illusion of control attitude and tend to be careful in making investment decisions. The absence of the influence of risk perception on investment decisions, because in this study the length of investment makes respondents make investment decisions that tend to like the risk and expect a good situation in the future.